Asymmetries of visual attention after circumscribed subcortical vascular lesions. Issue 5 (1st November 2001) - Fimm, B; Zahn, R; Mull, M; Kemeny, S; Buchwald, F; Block, F; Schwarz, M
Abstract : OBJECTIVE: To investigate the role of the basal ganglia and the thalamus for basic processes of visuospatial attention METHODS: Fifteen patients with acute circumscribed vascular lesions (10 with haemorrhage and five with infarction) were included in the study. The lesions were confined exclusively to subcortical structures, such as the basal ganglia, internal capsule, and thalamus, which was confirmed by initial CT on the day of referral and MRI taken 14–28 days after clinical onset. These patients were examined with two computerised attentional tasks (one detection and one search task) measuring spatial visual attention. RESULTS: There was a clear attentional asymmetry in patients with right hemispheric lesions (RHLs) in the visual search task. Seven out of eight patients with RHLs tended to be slower and/or missed significantly more target stimuli in the left sided part of a stimulus array consisting of 25 small squares than in right sided parts, although none of these patients showed signs of visual hemineglect in the visual detection task presenting visual information simultaneously to the right and left visual hemispace. All but one of these patients showed lesions in the posterior limb of the internal capsule and the putamen. On the other hand, patients with left hemispheric lesions were not impaired in the search task with only one patient showing more contralesional omissions of target stimuli than could be expected from the behaviour of normal controls. CONCLUSIONS: The results are in line with previous results showing a dominant role of right hemispheric neuronal structures for spatial attention. Furthermore, the data suggest that even with right hemispheric subcortical lesions without cortical involvement deficits in spatial orienting of attention to the left hemispace can be seen. These asymmetries of visual attention in the absence of neglect symptoms are supposed to be caused (1) by a disruption of the motor corticostriato-pallidothalamo-cortical neuronal circuit or (2) by a (partial) disconnection of relevant parts within the posterior attention network—namely, parietal and thalamic structures.